A comparative study of collagen-based dressing versus conventional dressing in chronic ulcers - Chaurasia, Shrashti; Diwaker, Arvind; Garg, Nitin (International Journal of Research in Medical Sciences, 2021)
Background: Collagen is a fibrous structure, proline-rich protein, comprised of three α-chains, plays an important role in each stage of wound healing, attracts fibroblasts and keratinocytes which in turn encourages debridement, angiogenesis and re-epithelialization Methods: This is a prospective cohort study. After obtaining ethical clearance from Institute’s ethical committee, all the patients fulfilling inclusion criteria were enrolled and written consent was obtained from all the patients. Detailed history was enquired and recorded on a predesigned proforma. The ulcer healing, analysed as- Time required for appearance of healthy granulation tissue, 50% reduction in ulcer size, complete healing time, requirement of skin grafting, time required in return to daily activities. Results: A significant decrease in time required for 50 % reduction in wound size with a mean difference of 18.5 in collagen group patients when compared to 37.5 and 33.0 in Normal saline group patients and Povidone iodine group patients. Chi square test was applied to assess the difference in proportions between groups t test was applied to compare the mean between the groups. P<0.05 was considered as statically significant. Conclusions: Healing with collagen particles is early, compared to the conventional dressings with lesser requirement of skin grafting, number of dressings, shorter hospital stay. Dressing changed every 3-4 days. Healing occurs by formation of early granulation tissue and wound contraction.